Improvement of enteral nutrition technologies in patients with a severe course of acute pancreatitis - Halil, Uzun; Kolosovych , Ihor; Hanol , Ihor (The Ukrainian Scientific Medical Youth Journal, 2023)
in the case of severe acute pancreatitis, the early start of enteral nutrition (24-72 hours from the moment of hospitalization) by means of nasogastric or nasojejunal administration of the mixture is considered appropriate, which is associated with a 24% decrease in the frequency of infectious complications and a 32% decrease in mortality. However, 30.5-65.7% of patients may develop intolerance to this type of nutritional support. The aim of the study was to improve the results of treatment of patients with severe acute pancreatitis by improving enteral nutrition technologies. There were 101 patients with severe acute pancreatitis took part in the study, who were divided into the main group, where enteral nutrition was carried out according to the improved protocol - 34 patients, comparison group No. 1, where standard nasogastric nutrition was carried out - 34 patients, and comparison group No. 2, where standard EN – 33 patients. The effectiveness of enteral nutrition in the studied groups was evaluated by analyzing and comparing biochemical indicators of blood serum, frequency of intolerance to nutritional support, infected local complications, mortality, duration of multiple organ failure and stay of patients in the hospital. When using the proposed protocol of enteral nutrition in patients with a severe course of acute pancreatitis, 14 days after the start of treatment, a significant difference was obtained between the content of albumin, creatinine, cholesterol and K+ blood serum (p<0.05) between patients of the main group and the comparison groups , as well as the content of Na+ in blood serum (p<0.05) between patients of the main group and the group of standard nasogastric tube feeding. Application of the proposed protocol of enteral nutrition significantly reduces the frequency of intolerance of nutritional support in the first 7 days of treatment by 23.6% (χ2=5.7, 95% CI 4.41-41.56, p=0.01) compared to the control group patients, where standard nasogastric tube feeding is used, by 21.5% (χ2=4.87, 95% CI 2.34-39.48, p=0.02) compared to the group of standard enteral tube feeding, as well as the duration of multiple organ failure from 12.2±1.7 days to 10.5±1.9 days in comparison with the group of patients where standard nasogastric tube feeding was used (p=0.0002) and from 11.5±1.9 days to 10.5±1.9 days compared to the group of standard enteral tube feeding (p=0.03). The use of the proposed technology of enteral nutrition in patients with a severe course of acute pancreatitis improves treatment results by reducing the duration of multiple organ failure and the frequency of intolerance to this type of nutritional support.